The Meaning of Verb Washin Javanese Nganjuk: A Natural Semantic Metalanguage Approach - Fitriana, Ita (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze and describe application of Natural Semantic Metalanguage (NSM) theory to verb “wash” in Javanese, Nganjuk dialect. Main theory of this research in NSM theory to analyze the data qualitatively through equivalent and sharing methods. Natural Semantic Metalanguage recognizes the principle that natural state of a language is to maintain form for one meaning and one meaning for one form. There are 2 data sources to complete this research: (1) primary data as verbal data and written data of research topic. Observation and interview are the methods of collecting data. Data analysis results are presented in both formal and informal methods. Results obtained show that verb “wash”/ ngumbah in Javanese consists of lexicons raup, wisuh, umbah-umbah, korah-korah, ngguyang, jamas, ngorek, ados, and wudhu. Those are having the same meaning, yet each lexicon has its own unique key feature to distinguish one to another.